Renal clearable catalytic gold nanoclusters for in vivo disease monitoring - Loynachan, Colleen N.; Amini, Ava; Dudani, Jaideep S.; Lin, Yiyang; Najer, Adrian; Bekdemir, Ahmet; Chen, Qu; Bhatia, Sangeeta N.; Stevens, Molly M. (Nature Nanotechnology, 2019)
Ultrasmall gold nanoclusters (AuNCs) have emerged as agile probes for in vivo imaging, as they exhibit exceptional tumour accumulation and efficient renal clearance properties. However, their intrinsic catalytic activity, which can enable an increased detection sensitivity, has yet to be explored for in vivo sensing. By exploiting the peroxidase-mimicking activity of AuNCs and the precise nanometre-size filtration of the kidney, we designed multifunctional protease nanosensors that respond to disease microenvironments to produce a direct colorimetric urinary readout of the disease state in less than one hour. We monitored the catalytic activity of AuNCs in the collected urine of a mouse model of colorectal cancer in which tumour-bearing mice showed a 13-fold increase in colorimetric signal compared to healthy mice. The nanosensors were eliminated completely through hepatic and renal excretion within four weeks of injection with no evidence of toxicity. We envision that this modular approach will enable the rapid detection of a diverse range of diseases by exploiting their specific enzymatic signatures. Catalytic gold nanoclusters that respond to protease activity in vivo and are excreted in urine can offer a quick colorimetric tool for disease detection in resource-limited settings.